The Application of Magneto-Rheological Elastomer in a Base Insolation System for Seismic Mitigation of Highway Bridges - Paschoalini, Amarildo Tabone [UNESP]; de Almeida, Fernanda Carolina [UNESP]; Proença, Matheus Silva [UNESP]; de Carvalho, Henrique Edno Leoncini [UNESP]; de Sousa Obata, Daniel Henrique [UNESP]; Fukushima, Jeferson Camargo [UNESP] (Springer Nature, 2025)
In recent years, the implementation of damping systems in civil structures has gained considerable attention, with emphasis on special building projects under dynamic loadings. In this scenario, due to their mechanical simplicity and controllable properties, Magneto-Rheological Elastomer (MRE) has stood out as providing an interesting alternative for vibration isolation. In these materials, the magnetic particles present in the elastomeric matrix are easily polarized in the presence of an external magnetic source, generating non-linear and reversible changes in the material, within a few milliseconds. In this way, the present work investigated numerically the efficiency of a certain damping system with MRE in isolating vibrations at the base of a bridge superstructure. The elastomer was simulated as a visco-elastic material of Kelvin–Voigt, and its stiffness and viscosity were regulated for five different scenarios. The unidimensional equivalent mechanical model was considered a single-degree-of-freedom (SDOF) system, and the ground motion generated by seismic excitations corresponded to shear excitations at the base. The base-isolated tests provided acceleration transmissibility under the different applied magnetic fields. It was observed that the viscoelastic support (VS) was able to shift the resonance frequency and the attenuation of transmissibility peak efficiently through field control. Moreover, with an adequate approach in the frequency domain, the random signal of a real earthquake was also inserted into the system for the evaluation of the isolator material. The findings demonstrated the good performance of the proposed MRE and its possibility of seismic vibration mitigation.
Keywords: Damping systems; Magneto-rheological elastomers; Vibration isolation